Implementation of Teacher Social Competence in Improving Student Learning Motivation - Ybnu Taufan, Muhammad; Basalamah, Abdurahman (Golden Ratio of Social Science and Education, 2021)
The purpose of this study was to examine the social implementation of teachers in increasing student motivation at Madrasah Tsanawiyah Negeri Balang-Balang, Gowa Regency. This research is qualitative because this type of research does not only want to collect data in terms of quality, to gain a deeper understanding. The study uses purposive sampling as well as a purposeful sample. The purpose of the sample is to take the subject based on the existence of that purpose. The sources of data in this study are the Head of Madrasah, Teachers, Student totaling 641 people. The population of this study amounted to 641 people, the authors used 10% of the total population, namely 64 students. Further data collection by observation, interviews. Qualitative data analysis techniques according to Matthew Milles consist of three streams of activities that occur simultaneously, namely: data reduction, data presentation, and verification or drawing conclusions. Results showed that the competence implementation factor encountered by the students' enthusiasm did not understand the teacher's wishes which resulted in their motivation to study being mediocre. Furthermore, the increase in teacher motivation also often carries out remedial and enrichment, because students often miss lessons so that special guidance is needed in this case.